2005
DOI: 10.4141/a04-038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding wheat straw and middlings ensiled with whey on digestibility and growth of cattle

Abstract: . 2005. Effects of feeding wheat straw and middlings ensiled with whey on digestibility and growth of cattle. Can. J. Anim. Sci. 85: 69-74. Two studies were conducted with the objective of evaluating the effects of feeding different levels of whey ensiled with wheat straw and wheat middlings (whey silage) compared to control diets on production parameters in growing cattle. Whey silage was included in diets at 55 and 65.5% on a dry matter basis with net energy for maintenance and crude protein calculated to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
4
6
0
Order By: Relevance
“…In our study, the digestibility of NDF and ADF increased significantly in WM diet compared with the other dietary treatments (P= 0.035 and P=0.035, respectively); consequently, also hemicellulose and cellulose digestibilites were higher in rams fed WM diet (P=0.041 and P=0.044, respectively). The present results are in agreement with ZoBell et al (2005) who reported a positive digestive trend, even if not significant, of DM and ADF digestibility in cattle fed 50% of WM in diet. Previous trials have reported that dietary WM in finishing steers and dairy cows led to a decrease of the digestibility of fibre components as WM level increased (Dalke et al 1997;Soares et al 2004).…”
Section: Resultssupporting
confidence: 96%
See 3 more Smart Citations
“…In our study, the digestibility of NDF and ADF increased significantly in WM diet compared with the other dietary treatments (P= 0.035 and P=0.035, respectively); consequently, also hemicellulose and cellulose digestibilites were higher in rams fed WM diet (P=0.041 and P=0.044, respectively). The present results are in agreement with ZoBell et al (2005) who reported a positive digestive trend, even if not significant, of DM and ADF digestibility in cattle fed 50% of WM in diet. Previous trials have reported that dietary WM in finishing steers and dairy cows led to a decrease of the digestibility of fibre components as WM level increased (Dalke et al 1997;Soares et al 2004).…”
Section: Resultssupporting
confidence: 96%
“…In a study, Cromwell et al (2000) recognized a greater variation in nutrients in grain Control, diet containing corn as the main grain source in total mixed ration; WM, diet containing wheat middlings as the main grain source in total mixed ration SEM standard error of mean (n=4 for each treatment) by-products than in feed grains and suggested more vigorous feed testing when by-products are used to ensure that ruminants are fed to satisfy nutrient requirements. In addition, the dissimilarity in results on feeding WM could be partly attributable to the differences in the digestibility of TMR diets when combinations of corn grain and forage, such as oat or barley hay, were fed along with WM and due to the variability in the nutrients in WM, as previously found also by ZoBell et al (2005) in growing beef cattle. The carcass characteristics and body measurements were similar between the two ewe lamb groups (Table 4).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Because of the mixture of coarse and fine particles and highly fermentable carbohydrates, WM must be evenly mixed in diets (ZoBell et al, 2003). The gross nutrient profile of WM indicates that it has a feeding value similar to that of cereal grains (with the exception of high fiber), and therefore may be used either in whole or part to replace the grain component in ruminant rations (ZoBell et al, 2005). Wheat middlings have been fed to livestock species such as poultry (Laudadio and Tufarelli, 2010), swine (Kim and Lei, 2005), and dairy and beef cattle (ZoBell et al, 2005;Bargo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%